KONTRIBUSI MANAJEMEN KEARSIPAN TERHADAP KUALITAS LAYANAN TENAGA PENDIDIK DI MTsN KOTA DAN KABUPATEN SERANG - Khaerudin Khaerudin (Jurusan Manajemen Pendidikan Islam Fakultas Tarbiyah dan Keguruan UIN Sultan Maulana Hasanuddin Banten, 2018)
This study aims to: (1) describe the great ways to manage archive at MTs Serang City, (2) describe the large-scale servive of educators in MTsN Serang District, (3) analyze wheter there are things related to archive management towards the quality of service of teaching staff at MTs Serang City and District. Analyze data by correlation method. Data was collected through a quetionnaires, interviews, documentations, and literatures. Population in this research is part of MTsN in Serang District and City, namely MTsN 1 in Serang City, MTsN 2 in Serang City, MTsN 1 Serang, and MTsN 3 Serang. The sample is 30 respondents from the sample with purposive sampling technique. Research result (1) the level of achievement of archival management of 83.45% is included in the excellent category; (2) the level of service quality of educators is 84.59% included in the excellent category; and (3) the contribution of archival management to the quality service of educatiors by using formula Product Moment is a 0.432. Determination coefficient of 19% which shows archives has an influence on the variable quality of service of educators by 19% and the rest by other factors such as facilities and infrastructure. Keywords. Archive management, quality of service.